The Influence of Steel Fiber on the Stress-Strain Behavior of Confined Concrete - Widayat Amariansah; Rinda Karlinasari (Universitas Islam Sultan Agung, 2019)
This paper presents the result of an experimental study of confined concrete to evaluate the stress-strain behavior of fiber-reinforced concrete, which includes strength and ductility. The effectiveness of steel fibers in influencing the stress-strain behavior was also evaluated by creating a conventional concrete as a control specimen. The experimental results showed that there was a decrease in the value of the increased strength of confined concrete (f’cc/f’co) when the compressive strength of the concrete increased. Reducing the spaces of lateral reinforcement spaces will also increase the strength and ductility of confined concrete. The comparison of experimental results with various confinement models shows that there are substantial differences in the peak stress and the descending behavior of confined fiber concrete.